Perancangan Iklan Poster Digital “STOP BULLYING” Berbasis Instagram @fisipunsri - Adam, Ryan (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2023)
Abstract. Cases of bullying are still common in Indonesia. This case is not only found in elementary schools, but also occurs in university. The increase in cases of bullying continues to increase every year. Starting from verbal bullying to bullying with physical violence. This causes the victim has an experience psychological traumatize, even having the desire to commit suicide. One of the efforts to prevent this from happening again is to make a public service advertisement using a digital poster